Human security : theory and action - Andersen-Rodgers, David; Crawford, Kerry F (Lanham, Maryland: Rowman & Littlefield, 2023)
"This thoroughly revised second edition of a popular text explores the theory and application of concepts central to human security, the protection of individuals from harm. Through an examination of the critical questions and priorities, it grounds students in the conceptual roots as well as applications and challenges both in war and peacetime"--
Includes bibliographical references and index.
Keywords: Human security; Human rights